Reading Habit in the Internet Era* - Sridhar, M. S. (Journal of Information and Knowledge, 2021)
The Internet and the digital revolution have deeply and sharply divided users into ‘digital immigrants’ and ‘digital natives’ with linguistic whateverism. The society is more image based than text and chat-based than reading. Reading habit is neither unambiguously definable nor accurately measurable. Proxy measures like book-buying, visiting, and borrowing from library, citations and downloads, self-reporting opinion is used to assess reading habit. Aliteracy is a predominant characteristic of the Internet era. The digital technology and the Internet have substantially affected the reading process as well as reading habit. Our ability to concentrate and read or think deeply is destroyed by digital distractions. It looks like there is a decline in reading habit due to the onslaught of electronic media. Despite increase in leisure time and income as well as considerable increase in expenditure on other forms of entertainment there is no corresponding increase in the expenditure on reading materials. The typical nature of digital reading as against print reading is characterized by convenience, devoting less time, reading shorter texts, impatience, etc, with certain values of online users as well as cognitive behaviour of students. There is a need for continuing the reading habit of print era in the digital era. Even in scholarly reading, it is imminent that the thoroughness of reading is sacrificed for speed and quantity as more and more read only shorter articles or abstracts.